2008
DOI: 10.1161/circulationaha.107.719500
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Creatinine With Abnormal Hemodynamics and Mortality in Pulmonary Arterial Hypertension

Abstract: Background-Renal dysfunction predicts mortality in patients with cardiovascular disease. How renal dysfunction relates to hemodynamics and mortality in pulmonary arterial hypertension (PAH) remains unclear. Methods and Results-We performed a cohort study of 500 patients with World Health Organization group I PAH from 1982 to 2006 with data on demographics, comorbidities, medications, functional class, laboratory tests, exercise testing results, and hemodynamics. Serum creatinine (SCr) was determined on entry i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
100
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 41 publications
1
100
2
2
Order By: Relevance
“…An increase in serum creatinine level often reflects impaired renal perfusion (13,14). In our study, there was no relationship between creatinine level and right atrial pressure.…”
Section: Discussioncontrasting
confidence: 55%
“…An increase in serum creatinine level often reflects impaired renal perfusion (13,14). In our study, there was no relationship between creatinine level and right atrial pressure.…”
Section: Discussioncontrasting
confidence: 55%
“…Thus, the presence of underlying kidney disease might be higher than what is noted in our study in those patients with PH. Shah et al (26) reported that, among PH patients (n=500), higher serum creatinine was associated with higher death rates among those patients with RAP,10 mmHg. However, Shah et al (26) did not notice significant associations in those patients with RAP.10 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…Shah et al (26) reported that, among PH patients (n=500), higher serum creatinine was associated with higher death rates among those patients with RAP,10 mmHg. However, Shah et al (26) did not notice significant associations in those patients with RAP.10 mmHg. Data from the REVEAL revealed that renal insufficiency (assessed at the time of enrollment of participants into the registry) was associated with an increased risk for death (hazard ratio, 1.90; 95% CI, 1.33 to 2.72) (14).…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated the relationship between serum ES and clinical markers of exercise performance and function, specifically 6 MWD and NYHA-FC, and serum chemistries previously linked to outcomes in PAH, notably NT-proBNP (18)(19)(20), creatinine (21), and serum sodium (22) ( Table 2).…”
Section: Serum Endostatin Correlates With Clinical Markers Of Diseasementioning
confidence: 99%